Viability of Entomopathogenic Fungi (Metarhizium anisopliae) in Residual Media Maggots and Pupa Shell Waste - Irwanto Sucipto; Wildan Muhlison; Aprilia Pangestu Putri (Postgraduate, University of Mataram, 2025)
Metarhizium anisopliae is a fungus that acts as an entomopathogen, commonly used to control pest insects (Biological Control Agent). This saprophytic mushroom requires sufficient organic nutrients in the growth medium. Typically, rice or corn is used as the media; however, this poses a challenge as these grains are also consumed by humans as staple foods. Additionally, the price of rice and corn has been increasing steadily. Alternatively, organic materials like maggot residue and pupa shells are byproducts from maggot cultivation that contain high nutritional value but are not utilized optimally. This research aims to identify effective alternative media for the multiplication of Metarhizium anisopliae. The research method involved controlled, homogeneous, and sterile experimental conditions, using a completely randomized design with four treatments and six repetitions. The fungus showed a high conidia density in the control media (rice corn), measuring 15.5 x 108. In chicken manure, a high density of 14.4 x 108 was observed, while the media made from maggot residue and pupa shells showed very low densities of 2.08 x 106 and 6.25 x 106, respectively. This suggests the presence of antimicrobial peptides (AMP), fatty acids, various bacteria, and lignocellulose compounds in the maggot residue and pupa shells. Overall, the organic materials from maggot residue and pupa shells are not effective as growth mediums for the fungus Metarhizium anisopliae.